Pemberdayaan Anggota Melalui Efektivitas Pengelolaan Zakat Infaq Shodaqoh (ZIS): Studi kasus pada KSPPS BMT ItQan Bandung - Aulia, Oli Aulia; Elya Dasuki, Rima (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
Empowering members is one of the goals of cooperatives to improve the welfare of their members. Cooperatives must be able to provide benefits to members, both direct benefits and indirect benefits. In sharia cooperatives, one source of financing comes from zakat-infaq-shodaqoh (ZIS). ZIS is a mandate from the community that must be managed well so that it meets the expected goals. KPPS BMT ItQan is one of the cooperatives that has the public's trust to manage ZIS funds.The aim of this research is to analyze the collection and distribution of ZIS funds in order to empower the community. The research method used is qualitative descriptive methods where the techniques used in this research are interviews, observation and documentation. KSPPS MT ItQan has 3 (three) products that can empower members, namely ItQan Assembly Financing, Bakti Maslahah Financing and Sharia Business Development. ItQan assembly financing is the most superior product. The principles of ZIS fund management and Law No. 23 of 2011 concerning zakat management are followed in the administration of the zakat, infaq, and alms (ZIS) program. This includes the proper planning, collection, distribution, and utilization of ZIS fund management. KSPPS BMT ItQan Bandung is able to empower members to the maximum extent possible